If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + -2) = 5(x + 3) Reorder the terms: (3 + x)(x + -2) = 5(x + 3) Reorder the terms: (3 + x)(-2 + x) = 5(x + 3) Multiply (3 + x) * (-2 + x) (3(-2 + x) + x(-2 + x)) = 5(x + 3) ((-2 * 3 + x * 3) + x(-2 + x)) = 5(x + 3) ((-6 + 3x) + x(-2 + x)) = 5(x + 3) (-6 + 3x + (-2 * x + x * x)) = 5(x + 3) (-6 + 3x + (-2x + x2)) = 5(x + 3) Combine like terms: 3x + -2x = 1x (-6 + 1x + x2) = 5(x + 3) Reorder the terms: -6 + 1x + x2 = 5(3 + x) -6 + 1x + x2 = (3 * 5 + x * 5) -6 + 1x + x2 = (15 + 5x) Solving -6 + 1x + x2 = 15 + 5x Solving for variable 'x'. Reorder the terms: -6 + -15 + 1x + -5x + x2 = 15 + 5x + -15 + -5x Combine like terms: -6 + -15 = -21 -21 + 1x + -5x + x2 = 15 + 5x + -15 + -5x Combine like terms: 1x + -5x = -4x -21 + -4x + x2 = 15 + 5x + -15 + -5x Reorder the terms: -21 + -4x + x2 = 15 + -15 + 5x + -5x Combine like terms: 15 + -15 = 0 -21 + -4x + x2 = 0 + 5x + -5x -21 + -4x + x2 = 5x + -5x Combine like terms: 5x + -5x = 0 -21 + -4x + x2 = 0 Factor a trinomial. (-3 + -1x)(7 + -1x) = 0Subproblem 1
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 2
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Solution
x = {-3, 7}
| 4(x-3)+6(x+10)-15=-22 | | 8-2g+5g+3= | | 4(x-3)+6(x+10)-15=-23 | | 3x(3x^2-10x+3)=0 | | -12h=-60 | | 42=144 | | X+y=4z | | 3x^2+18+24= | | 2a+4=12a+6 | | a*a(a-2b)+3b(a*a-4)= | | t+15=20 | | =-4x^3+18x | | 1/3n4 | | -2p+1=5 | | (5x+7)-(3x-1)=22 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i+2=0 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i=0 | | 2x^2+5x+3=15 | | 22x^2+5x+3=15 | | 0.5x+2.49=-.07x+6.69 | | 1=b-13 | | 3cos^2x=7sinx+5 | | X-52=100 | | 7x+9y=107 | | 2-3x=-2-2x | | 8-1/4z=1 | | 3,6*4/0,6*8 | | 6v=198 | | 4(x+5)-24=5x-13 | | 13+n=23 | | 25=a/b | | 15=2x+5x+3 |